Scalable Process Design for a PDE10A Inhibitor Consisting of Pyrazolopyrimidine and Quinoxaline as Key Units - Yamagami, Takafumi; Kobayashi, Ryo; Moriyama, Noriaki; Horiuchi, Hideki; Toyofuku, Eiji; Kadoh, Yoichi; Kawanishi, Eiji; Izumoto, Shinichi; Hiramatsu, Hajime; Nanjo, Takehiro; Sugino, Masuhiro; Utsugi, Masayuki; et al. (Organic Process Research & Development, 2019)
In this study, research and development for the synthetic process of a PDE10A inhibitor are described; in particular, an efficient regioselective construction of the quinoxaline unit, a cost-effective pyrazolo[1,5-a]pyrimidine formation, and a cost-saving approach in a nucleophilic aromatic substitution (SNAr) reaction by introducing oxazolidinone as an electron-withdrawing group to a chloropyrazolo[1,5-a]pyrimidine core are key points. The newly developed process has been successfully scaled up to 40 kg. Furthermore, a one-pot tandem reaction from aminopyrazole to dichloropyrazolo[1,5-a]pyrimidine by activating malonic acid with POCl3 was discovered. The finding contributed to avoiding isolation of the hygroscopic pyrazolo[1,5-a]pyrimidin-5(4H)-one intermediate, which caused complicated filtration and drying processes observed in the first scale-up campaign.